Vocalisations of Antarctic blue whales, Balaenoptera musculus intermedia, recorded during the 2001/2002 and 2002/2003 IWC/SOWER circumpolar cruises, Area V, Antarctica - Rankin , Shannon; Ljungblad, Don; Clark , Chris; Kato, Hidehiro (J. Cetacean Res. Manage., 2023)
Blue whale vocalisations recorded during the 2001/2002 and 2002/2003 International Whaling Commission-Southern Ocean Whale and Ecosystem Research (IWC/SOWER) cruises were analysed to determine the feasibility of using acoustic recordings for sub-species identification of the Antarctic blue whale (Balaenoptera musculus intermedia) and the pygmy blue whale (B.m. brevicauda). The research was conducted in IWC Area V, from latitude 60°S to the ice edge and between longitudes 130°E and 150°E on the Shonan Maru (2001/2002), and between 150°E and 170°W on the Shonan Maru No.2 (2002/2003). Data including 15 groups consisting of 42 animals, as well as opportunistic recordings of an unknown number of animals during evening sonobuoy stations were examined for this study. Vocalisations included long-duration 28Hz tonal sounds and relatively short-duration frequency-modulated sounds. The short-duration calls were similar to vocalisations recorded in the presence of blue whales in other locations worldwide. Not all recordings contained the longduration 28Hz call, considered to be a species-specific vocalisation of Antarctic blue whales. None of the sounds that have previously been attributed to pygmy blue whales were detected. The long-duration 28Hz tonal vocalisations included 3-unit calls, considered to be song phrases, as well as simple 28Hz sounds and 28Hz sounds followed by a downsweep. The centre and peak frequencies of the 28Hz tone for these three sound types were stable regardless of signal strength; however, for the 3-unit vocalisation, the presence and characteristics of their 2nd and 3rd units were variable. Examination of two distinct groups of simultaneously vocalising blue whales showed no evidence of temporally repeated patterns of vocalisations (song phrases). The results of this study suggest that the peak frequency of the 28Hz vocalisations may be used as a diagnostic feature to aid in discriminating between Antarctic blue whales and pygmy blue whales in the field; however, examination of vocalisations in relation to group size and behaviour are necessary to understand the circumstances in which the 28Hz vocalisations are produced.